Analysis of colorectal cancer‐related mutations by liquid biopsy: Utility of circulating cell‐free DNA and circulating tumor cells. Issue 11 (18th September 2019) - Takeda, Kohki; Yamada, Takeshi; Takahashi, Goro; Iwai, Takuma; Ueda, Koji; Kuriyama, Sho; Koizumi, Michihiro; Matsuda, Akihisa; Shinji, Seiichi; Ohta, Ryo; Yokoyama, Yasuyuki; Hotta, Masahiro; et al.
Abstract: We recruited 56 colorectal cancer patients and compared the mutational spectrum of tumor tissue DNA, circulating cell‐free DNA (ccfDNA) and circulating tumor cell (CTC) DNA (ctcDNA) to evaluate the potential of liquid biopsy to detect heterogeneity of cancer. Tumor tissue DNA, ccfDNA, and ctcDNA were extracted from each patient and analyzed using next‐generation sequencing (NGS) and digital PCR. To maximize yields of CTC, three antibodies were used in the capture process. From 34 untreated patients, 53 mutations were detected in tumor tissue DNA using NGS. Forty‐seven mutations were detected in ccfDNA, including 20 not detected in tissues. Sixteen mutations were detected in ctcDNA, including five not detected in tissues. In 12 patients (35.3%), mutations not found in tumor tissues were detected by liquid biopsy: nine (26.5%) in ccfDNA only and three (8.8%) in ctcDNA only. Combination analysis of the two liquid biopsy samples increased the sensitivity to detect heterogeneity. From 22 stage IV patients with RAS mutations in their primary tumors, RAS mutations were detected in 14 (63.6%) ccfDNA and in eight (36.4%) ctcDNA using digital PCR. Mutations not detected in primary tumors can be identified in ccfDNA and in ctcDNA, indicating the potential of liquid biopsy in complementing gene analysis. Combination analysis improves sensitivity. Sensitivity to detect cancer‐specific mutations is higher in ccfDNA compared with ctcDNA. Abstract : Cancer is a heterogeneous disease. We compared the mutational spectrum of tumor tissue DNA, circulating cell‐free DNA, and circulating tumor cell DNA in colorectal cancer patients using next‐generation sequencing and digital PCR. Results showed the potential of liquid biopsy samples to provide a complementary role in genetic analysis.